Синтез та властивості нанокомпозитів CeO2/SiO2 - Kulyk, K. S.; Borysenko, M. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
Cerium dioxide cubic modification nanoparticles distributed in silica matrix were synthesized by impregnation and molecular layering methods in size range 3 – 25 nm. Prepared nanocomposites were studied using XRD, SEM, TG, DTA and low-temperature argon desorption technique.